Public private mix in tuberculosis control: is it really working in India? - Nautiyal, Ram Gopal; Singh, Rajesh Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: As significant proportions of the tuberculosis (TB) patients in India are managed by the private sector, integration of the private sector with the revised national tuberculosis control programme (RNTCP) is crucial to achieve TB control in the country. The RNTCP of India has been therefore involving allopathic private practitioners (PPs) since its beginning through its RNTCP- Indian Medical Association public-private mix (RNTCP-IMA PPM) project for inclusive involvement of PPs in the programme to fight against TB. The objectives of the study were to evaluate whether or not the RNTCP-IMA PPM project in India could mobilize the support of the allopathic private practitioners (PPs) by analyzing their knowledge and perception about RNTCP, and their readiness to support the programme. Methods: A questionnaire based cross- sectional study was conducted in urban areas of districts of Kumaon division of Uttarakhand State of North India. Results: Of 71 PPs, almost 83% knew that in RNTCP sputum acid fast bacillus (AFB) examination was the most important diagnostic test for pulmonary tuberculosis, 66.2% knew that intermittent regimens under direct observation are practiced in RNTCP, 32.4% believed drug regimens in RNTCP of questionable efficacy, 29.6% felt ignored by the programme and only 2.8% felt RNTCP a successful strategy. 50.7% PPs showed readiness to support the programme with government support. Conclusions: The RNTCP-IMA PPM project seems to have performed sub-optimally as majority (97.2%) PPs did not perceive RNTCP as a successful strategy. For successful RNTCP-IMA PPM, India needs to upscale the existing PPM with strong political will and administrative commitment.